Pengaruh Pemberian Ekstrak Etanol Buah Sirsak (Annona muricata L.) Pada Kadar Kolesterol Low Density Lipoprotein (LDL) Tikus Putih (Rattus norvegicus) Hiperkolesterolemia - Siti Fatimah; Desto Arisandi; Sismawati Sismawati (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
The cause of Coronary heart disease is an increase caused due to increased cholesterol levels in the blood, so there is a risk of blockage in the blood vessels (atherosclerosis). LDL cholesterol which is abundant in the bloodstream will accumulate in the arteries and potentially cause blockages. Ethanol extract of soursop fruit (Annona Muricata L.) contains antioxidant compounds such as alkaloids, tannins, saponins, flavonoids and polyphenols that are needed to increase endurance and prevent various diseases that enter the body. Research has been conducted to determine the effect of soursop fruit ethanol extract (Annona Muricata L.) on Low Density Lipoprotein (LDL) cholesterol levels white Rat (Rattus Norvegicus) hipercolesterolemia. This research was conducted experimentally with 10 male white rats (Rattus Novergicus, L.), aged 2-3 months with a weight of 150-200 g, which were divided into 2 groups: the control group and the treatment group. Hypercholesterolemia induction is done by giving high fat diet foods for 7 days. Soursop fruit ethanol extract was given in a sonde to the treatment group at a dose of 3.6 mg / 200gBB / day for 14 days and measurements of LDL cholesterol levels were carried out on days 16 and 30 by the CHOD-PAP examination method. Data were analyzed by Paired t-test. The results showed LDL cholesterol levels in the treatment group showed that as many as 5 mice decreased, the mean decreased by 32.49 mg / dl while in the control group as many as 2 mice decreased, the mean decreased by 0.76 mg / dl. There was a significant difference (p <0.05) in changes in LDL cholesterol levels in the treatment group. Soursop fruit etanol extract with 3.6 mg / 200gBB / day for 14 days can reduce LDL cholesterol levels in hypercholesterolemia rats.